Testing emergency language skills in situational teaching: a quasi-experimental research - Zhu, An; Wang, Jing; Li, Yan (Frontiers in Education, 2026)
Despite the growing recognition of the need for specialized training in emergency language skills, educational frameworks in which disaster scenarios are integrated into language pedagogy remain underdeveloped. Therefore, this quasi-experimental study is designed to investigate the efficacy of situational teaching methods in enhancing learners’ emergency language competencies. A quasi-experimental test is used to assess the participants’ ability to process and communicate information related to critical disasters in a multilingual environment by measuring their pre-test and post-test learning outcomes. The results indicate a statistically significant improvement in the application of emergency language skills, emergency professional knowledge, and the ability to communicate emergency language following the scenario-based training. These findings highlight that the use of context-driven teaching methods, compared to traditional teaching methods, helps to compensate for the deficiencies existing in the current educational framework and effectively enhances learners’ emergency language proficiency.